Melatonin Promotes Muscle Growth and Redirects Fat Deposition in Cashmere Goats via Gut Microbiota Modulation and Enhanced Antioxidant Capacity - Di Han; Zibin Zheng; Zhenyu Su; Xianliu Wang; Shiwei Ding; Chunyan Wang; Liwen He; Wei Zhang (Antioxidants)
Liaoning cashmere goats is a dual-purpose breed valued for premium cashmere fiber and meat yields, and there is currently a lack of optimized strategies for meat quality, including skeletal muscle development and lipid partitioning. This investigation systematically examines how melatonin administration modulates gastrointestinal microbiota and antioxidant capacity to concurrently enhance skeletal muscle hypertrophy and redirect lipid deposition patterns, ultimately improving meat quality and carcass traits in Liaoning cashmere goats. Thirty female half-sibling kids were randomized into control and melatonin-treated groups (2 mg/kg live weight with subcutaneous implants). Postmortem analyses at 8 months assessed carcass traits, meat quality, muscle histology, plasma metabolites, and gut microbiota (16S rRNA sequencing). Melatonin supplementation decreased visceral adiposity (perirenal, omental, and mesenteric fat depots with a p < 0.05) while inducing muscle fiber hypertrophy (longissimus thoracis et lumborum (LTL) and biceps femoris (BF) with p < 0.05). The melatonin-treated group demonstrated elevated postmortem pH24h values, attenuated muscle drip loss, enhanced intramuscular protein deposition, and improved systemic antioxidant status (characterized by increased catalase and glutathione levels with concomitant reduction in malondialdehyde with p < 0.05). Melatonin reshaped gut microbiota, increasing α-diversity (p < 0.05) and enriching beneficial genera (Prevotella, Romboutsia, and Akkermansia), while suppressing lipogenic Desulfovibrio populations, and concomitant with improved intestinal morphology as evidenced by elevated villus height-to-crypt depth ratios. These findings establish that melatonin-mediated gastrointestinal microbiota remodeling drives anabolic muscle protein synthesis while optimizing fat deposition, providing a scientifically grounded strategy to enhance meat quality.